Chronic contamination assessment integrating biomarkers' responses in transplanted mussels-A seasonal monitoring - Pereira, C. D. S.; Martin-Diaz, M. L.; Catharino, M. G. M.; Cesar, A.; Choueri, R. B.; Taniguchi, S.; Abessa, Denis Moledo de Souza [UNESP]; Bicego, M. C.; Vasconcellos, M. B. A.; Bainy, A. C. D.; Sousa, E. C. P. M.; DelValls, T. A. (Wiley-Blackwell, 2012)
This study aimed to provide the first biomonitoring integrating biomarkers and bioaccumulation data in São Paulo coast, Brazil and, for this purpose, a battery of biomarkers of defense mechanisms was analyzed and linked to contaminants' body burden in a weigh-of-evidence approach. The brown mussel Perna perna was selected to be transplanted from a farming area (Caraguatatuba) to four possibly polluted sites: Engenho D'Agua, DTCS (Dutos e Terminais do Centro-Oeste de São Paulo) oil terminal (Sao Sebastiao zone), Palmas Island, and Itaipu (It; Santos Bay zone). After 3 months of exposure in each season, mussels were recollected and the cytochrome P4501A (CYP1A)- and CYP3A-like activities, glutathione-S-transferase and antioxidants enzymes (catalase, glutathione peroxidase, and glutathione reductase) were analyzed in gills. The concentrations of polycyclic aromatic hydrocarbons, linear alkylbenzenes, and nonessential metals (Cr, Cd, Pb, and Hg) in whole tissue were also analyzed and data were linked to biomarkers' responses by multivariate analysis (principal component analysisfactor analysis). A representation of estimated factor scores was performed to confirm the factor descriptions and to characterize the studied stations. Biomarkers exhibited most significant alterations all year long in mussels transplanted to It, located at Santos Bay zone, where bioaccumulation of organic and inorganic compounds was detected. This integrated approach using transplanted mussels showed satisfactory results, pointing out differences between sites, seasons, and critical areas, which could be related to land-based contaminants' sources. The influence of natural factors and other contaminants (e.g., pharmaceuticals) on biomarkers' responses are also discussed. (C) 2010 Wiley Periodicals, Inc. Environ Toxicol, 2012.
Keywords: biomarkers; bioaccumulation; Perna perna; multivariate analysis; biomonitoring